PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS ANDROID PADA MATA PELAJARAN INFORMATIKA DI SMK NEGERI 3 TEBO - S, Rimba Darmanda; Rini, Faiza; Kurniawan, Haris (Universitas Muhammadiyah Tapanuli Selatan, 2024)
The problem that exist in the informatics subject in computer network and internet material at SMK Negeri 3 Tebo is that there is not Android-based learning media that is used as a supporting medium in the learning process.Â This The ADDIE development model and Research and Development (RD) method were used in dhis study. A total of 26 students were sampled in this study. The data collection technique used a questionnaire with a likert scale. The result of this study indicate that the average value of the media expertâ€™s validity test is 85.24% with the valid category and the material expert is 85.55% with the valid category. For the practicality test on the teacherâ€™s response it reached 93.33% in the very practical category and for student responses it reached 85.33% in the very practical category.